ANALISIS WACANA KRITIS TERHADAP KOMENTAR NEGATIF TERKAIT CHILDFREE DI MEDIA SOSIAL DENGAN PERSPEKTIF SARA MILLS - Ari Musdolifah; Fadhilah Azzahra; Mia Maulidia; Nasywa Haniifa Budiono; Syarifullah Yusuf; Isar Darmawan (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This study analyzes the negative comments received by childfree women on social media, focusing on the Instagram account @indo_psychology and X account @tanyarlfes using Sara Mills' critical discourse analysis model. This research explores how the language in the comments reinforces social norms that assume women's main role is as mothers. This research uses a qualitative descriptive method. The research data was collected from the comments posted in both accounts. Sara Mills' critical discourse analysis approach was applied to analyze the subject, object, and reader in the six comments of Instagram account @Indo_Psychology and X account @tanyarlfes. The two social media accounts are Subjects and Childfree as Objects. The results show that negative comments often contain views that blame and shame childfree women, affecting people's perceptions and reinforcing social stigma. This research focuses on countering negative stereotypes and promoting gender equality in society.